Impact of alternative synthetic turf infills on athlete performance and safety - Dickson, K.; Sorochan, J.; Strunk, W. (Proceedings, 2020)
The objective of this study is to determine the impact of three alternative infills of various particle size on athlete performance and safety in a third generation (3G) synthetic fields. A complete randomized design composed of three different infill materials (thermoplastic elastomer, coconut and cork mixture, and recycled Nike shoes (Nano)) with all infills having the same infill depth, fiber length, fiber density, and shock pad. The study took place at the Center for Athletic Field Safety (CAFS) during the summer of 2017 in Knoxville, TN. Each plot received 120 traffic events with the CAFS traffic simulator. This study found that alternative infills do impact the safety and performance of the field, while showing a variation of performance properties among the alternative infills. The results of this study indicate that particle size and distribution of the infill plays a key role in the superior field performance in 3G turf.